CONSULTATIO VETERIS CUIUSDAM IURISCONSULTI ROZDZIAŁ IX ZAGADKOWEGO TEKSTU I JEGO PRZEZNACZENIE - Chmiel, Piotr (Zeszyty Prawnicze, 2017)
CONSULTATIO VETERIS CUIUSDAM IURISCONSULTI Chapter IX of the Mysterious Text and its Purpose Summary The article presents the common opinion about an enigmatic Roman legal text from the Vth century, called Consultatio veteris cuiusdam iurisoconsulti. This short text, published for the first time in 1577 by J. Cujas, is composed of some fragments from the codes Gregorian and Hermogenian, The Tedosian Code and Pauli Sententiae, with comments explaining the legal institutions mentioned in those fragments. According to the researchers, the text was probably composed in the second half of the Vth century, in Gaul or northern Italy. The text can be easily divided into three parts which could have been formulated by different authors or – which seems to be more probable – by the same author, vetus iurisocnsultus, who presented the problems useful for a teacher in a legal school, a bishop during an episcopalis audientia and a law operator. One of the more interesting parts of the Consultatio is chapter IX, composed of only 19 fragments of imperial constitutions without any comments.